KONSUMSI ZINC TERHADAP PENYEMBUHAN LUKA PERINEUM DAN PENURUNAN SKALA NYERI : A LITERATURE REVIEW - Yunisra Ikasari; Listyaning Eko Martanti; Sri Sumarni (Midwifery Care Journal, 2021)
Perineum wounds that occur in most childbirth need to be healed immediately to prevent infection and lower the scale of pain. Perineum wound healing is influenced by many things, one of which is zinc. The purpose of this study was to find out the effect of zinc on perineum wound healing and the relationship of perineum wound healing with decreased pain scale. The research design uses literacystudies,  searches using proquest sites and google scholar. Originally found 218 articles,  186 articles were eligible after duplication checks. Articles are filtered by publication time, article type, and full text availability. The articles covered are articles published in the last 10 years (2011 and above). The types of articles discussed are articles that are not literature studies. This filtering resulted in 86 articles. Articles that are not relevant to zinc, wound healing and decreased the scale of perineum pain in  eksklusi,  so obtained  11 articles that became samples in the study. Zinc is able to accelerate the healing of perineum wounds. However, its effectiveness in accelerating wound healing is still less when compared to vitamin C. Zinc will be more effective in accelerating wound healing if combined with other therapies such as honey and vitamin C. Zinc is safe to be consumed safely by humans with a maximum limit of 40mg/day. There is a link between perineum wound healing and decreased pain scale. This research is expected to be an input for health workers, especially midwives to provide zinc tablet therapy for mothers nifas to accelerate the healing of perineum wounds.